Understanding Conservation Conflicts in Uganda: A Political Ecology of Memory Approach - Akampurira, Emmanuel (Conservation and Society, 2023)
Political ecologists have linked conservation conflicts in post-independence Africa to the continuities and legacies of colonial policies that displaced and dispossessed people to create ‘wild places’. This paper introduces a political ecology of vernacular memory to discuss the Basongora people’s vernacular memories of their historical dispossession to create the Queen Elizabeth National Park (QENP) in Uganda. It explores how these events spurred multidirectional memories of resilience, heroism, victimhood, and resistance that the Basongora pastoralists deploy to reclaim social-political autonomy and agency. Using archival data and historical ethnography, I examine how the Basongora mobilise vernacular memory in contemporary contestations with the state and conservation authorities in QENP. Vernacular memory provides a moral authority that helps subordinated groups contest the hegemonic dominance of conservation authorities. A political ecology approach to vernacular memory reveals how people use memory politics to legitimise their claims in contested environments—an essential fact of contemporary conservation conflicts. This paper is the first to conceptualise how vernacular memories can legitimise the decolonisation of conservation narratives and community resistance against conservation.
Keywords: Political ecology; Conservation conflicts; Vernacular memory; Colonisation; Basongora; Agency